Proteomics study of N‐acetylcysteine response in H1N1‐infected cells by using mass spectrometry. (13th February 2014) - Wu, Hanzhi; Song, Wenjun; Gao, Xiang; Liu, Ning; Wang, Pui; Chen, Honglin; Cai, Zongwei
<x xml:space="preserve">Abstract</x> RATIONALE The pathology of A/Puerto Rico/8/1934 (H1N1) infection associated with the interaction of virus and its host cells is not clear. N‐Acetylcysteine (NAC) is an antioxidant as well as a premier antitoxin and immune support substance. A high dose of NAC was recently reported for a therapy of H1N1 (2009) influenza pneumonia. METHODS NAC was used as a small‐molecule organic probe to investigate the protein expression of human lung carcinoma cell line (A549) infected by influenza virus A/Puerto Rico/8/1934 (H1N1). Differential proteins were identified from MALDI‐TOF MS and Q‐TOF MS/MS analyses. RESULTS The obtained results showed that NAC kept cells away from apoptosis. Virus‐infected cells were arrested in G0/G1 phase. The lowest cell population of G0/G1 phase was detected when the cells were treated by 10 mM NAC for one day. Application of MS‐based proteomics allowed the identification of the differential proteins. Software analysis showed that four proteins had close relationship. CONCLUSIONS The results indicated that NAC as a small‐molecule probe might effect the protein expression of A549 cells infected by the H1N1 virus. Copyright © 2014 John Wiley & Sons, Ltd.